2015
DOI: 10.1080/10810730.2014.999894
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Tone of Ontario Newspaper Articles on the Health Effects of Industrial Wind Turbines Before and After Policy Change

Abstract: Newspapers are often a primary source of health information for the public about emerging technologies. Information in newspapers can amplify or attenuate readers' perceptions of health risk depending on how it is presented. Five geographically distinct wind energy installations in Ontario, Canada were identified, and newspapers published in their surrounding communities were systematically searched for articles on health effects from industrial wind turbines from May 2007 to April 2011. The authors retrieved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Based on the earlier findings on negative tone in the news coverage of certain health risks (Deignan & Hoffman-Goetz, 2015; H. Lee & Len-Rios, 2014), we predict that the tone of the MERS editorials and columns would be negative.…”
Section: Analytic Paradigms For Infectious Disease Editorialsmentioning
confidence: 93%
See 2 more Smart Citations
“…Based on the earlier findings on negative tone in the news coverage of certain health risks (Deignan & Hoffman-Goetz, 2015; H. Lee & Len-Rios, 2014), we predict that the tone of the MERS editorials and columns would be negative.…”
Section: Analytic Paradigms For Infectious Disease Editorialsmentioning
confidence: 93%
“…This attribute of affect can be transferred to health risk perception as well. Therefore, the news coverage on health issues such as the “health effects of industrial wind turbines” (Deignan & Hoffman-Goetz, 2015), “tobacco” (Blake, Kaufman, Lorenzo, & Auguston, 2015), or “obesity” (H. Lee & Len-Rios, 2014) has been examined in terms of the affective tone.…”
Section: Analytic Paradigms For Infectious Disease Editorialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies from Australia include Djerf-Pierre et al 2015, Hindmarsh (2014) and Romanach et al (2015). One study examines Canada (Deignan and Hoffman-Goetz, 2015). Djerf-Pierre et al, 2015).…”
Section: National Structural Conditions As Influencing Factors On Thementioning
confidence: 99%
“…This includes the potential, demand, supply and usage of energy resources. Previous research has shown that such factors might play a role in how renewable energy is covered in the media (Skjølsvold, 2012;Deignan and Hoffman-Goetz, 2015;Djerf-Pierre et al, 2015). The second factor is a focusing event, in this case the Fukushima nuclear catastrophe.…”
Section: Introductionmentioning
confidence: 99%